2003
DOI: 10.1017/s0031182002002512
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in the reproductive organs of male and female Schistosoma mansoni worms caused by streptozotocin, a drug used to induce diabetes mellitus

Abstract: Host metabolic changes have been observed to affect Schistosoma mansoni egg production, worm survival and morphology. We examined worms recovered from streptozotocin-induced diabetic mice by morphometric and morphological analysis through brightfield and confocal laser scanning microscopy. Tegument thickness was slightly smaller and changes in the reproductive organs were observed in 23-30% and consecutively 88-100% of the worms. The testicular lobes had a large diminution of cells in one or more of the lobes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…The lobes of these supernumerary testes contain variable amounts of fully developed oocytes instead of a testicular mass (Hulstijn et al, 2003). The lobes of these supernumerary testes contain variable amounts of fully developed oocytes instead of a testicular mass (Hulstijn et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The lobes of these supernumerary testes contain variable amounts of fully developed oocytes instead of a testicular mass (Hulstijn et al, 2003). The lobes of these supernumerary testes contain variable amounts of fully developed oocytes instead of a testicular mass (Hulstijn et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Different endohelminths of fish were suggested as sentinel organisms to detect metal pollution in aquatic habitats [1]. Most of the available papers emphasize adult intestinal parasites such as acanthocephalans (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available papers emphasize adult intestinal parasites such as acanthocephalans (e.g. Pomphorhynchus laevis, Acanthocephalus lucii ), which have a remarkable capacity to accumulate heavy metals [1,2] at concentrations many hundred to a thousand times higher than their host tissues and the aqueous environment [3,4]. With the use of these parasites even low levels of environmental pollution can be detected [5], which is often impossible using conventional analytical methods and/or free living sentinels such as mussels [6].…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomes are blood-dwelling flukes that are highly dependent on the host metabolism (Saule et al 2005). As a result, physiological changes associated with schistosomiasis infection have been considered important factors influencing this host-parasite relationship (Hulstijn et al 2003). Early studies showed dramatic alterations in adult worm development (Neves et al 2001, as well as diminished schistosomal periovular granuloma and milder chronic lesions in undernourished mice compared to mice fed a normal diet .…”
mentioning
confidence: 99%